FTIR spectroscopy and machine learning for detection of Sudan I dye as a hazardous contaminant in turmeric powder - T. Vignesh; D. Selvakumar; P.Y. Mallikarjun; N.K. Geetha; S. Madhankumar; Mandar Jatkar (Journal of Environmental Chemical Engineering, 2026)

Retraction notice to “Persistent organic pollutants in water resources: Fate, occurrence, characterization and risk analysis” [Sci. Total Environ. 831 (2022) 154808] - J. Aravind Kumar; T. Krithiga; S. Sathish; A. Annam Renita; D. Prabu; S. Lokesh; R. Geetha; S. Karthick Raja Namasivayam; Mika Sillanpaa (Science of The Total Environment, 2026)

Plant Probiotics Modulate Physio-biochemical Characteristics of Vigna Radiata Cultivars Under Polyethylene Glycol Induced Drought Stress - Vinoth Kumar Muniyappan; K. Sundaralingam; U. Sivakumar; V. Vijaya Geetha; T. Murugeshwari (Journal of Soil Science and Plant Nutrition, 2026)

Personalizing treatment of pancreatitis-associated chronic pain: the need for an integrated omics approach - Cole Myers; Cheyenna M. Espinoza; Aaron Clarke; Elizabeth R. Lusczek; Feng Xie; Brian T. Steffen; Zeribe C. Nwosu; Guru Trikudanathan; Geetha Saarunya; Melena Bellin; Gregory Beilman (Inflammation Research, 2026)
Background Chronic pancreatitis (CP) is a progressive inflammatory disorder characterized by debilitating chronic pain and substantial healthcare burden. Pain mechanisms in CP are heterogeneous and incompletely integrated into clinical decision-making. This narrative review synthesizes data from human CP cohorts and complementary experimental models to summarize inflammatory, neuropathic, and metabolic drivers of pancreatitis-associated pain and to evaluate how integrated multi-omics approaches may enable mechanism-based precision management. Current treatment relies on lifestyle modification, anatomy-guided interventions, stepwise pharmacologic escalation, and surgery for refractory cases. Emerging ion-channel–targeted therapies show promise, but inconsistent patient selection and limited biomarker guidance constrain therapeutic precision. Findings CP-associated pain arises from convergent inflammatory, neuroimmune, neuropathic, and metabolic pathways that promote peripheral and central sensitization with sustained neuroplastic remodeling. Advances in clinical phenotyping have improved characterization of pain subtypes; however, integration of biologic data remains limited. Genetic association studies increasingly implicate pathways linked to severe or persistent pain phenotypes. Omics investigations have identified candidate genomic, proteomic, and metabolomic signals that may support biologically informed stratification and treatment prediction. Nevertheless, most studies are cross-sectional, modality-specific, and derived from heterogeneous cohorts with inconsistent endpoints and limited external validation. Conclusions Integration of rigorous clinical phenotyping with longitudinal, multi-omics modeling provides a framework for developing testable, mechanism-based biomarkers to guide personalized analgesic and procedural strategies while supporting opioid-sparing care. Priorities include harmonization of multicenter datasets, standardized and longitudinal pain outcome measurement, expanded paired biospecimen collection, and external validation of predictive models. Such efforts may enable biologically grounded pain stratification and facilitate translation of biomarker-guided decision tools into routine clinical practice.

An improved Glucocerebrosidase Assay for Accurate Prediction of Lysosomal Dysfunction: Exemplified by Its Relevance in Parkinson’s Disease - Aishwarya Babu; Achanya S. Jayan; Anjali Sethumadhavan; Geetha Mandagini; Cibin T. Raghavan; Srinivas Gopala; Syam Krishnan; Madhusoodanan Urulangodi (Indian Journal of Clinical Biochemistry, 2026)

Thermal Conversion of Sugarcane Bagasse to Biochar and Its Application in Treatment of Methylene Blue Contaminated Water - T. Geetha; John K Smitha; Litty Mathew Irimpan; Manju Sebastian; V. Geetha; C. J. Theresa; Bincy Joseph; M. Nancy; K. Nimmy (Sugar Tech, 2026)

Aquaculture of Asian seabass (Lates calcarifer) in India: A comparative economic analysis across production systems and regions - Geetha R.; Abhinaya D.; Naffees Gowsar S. R.; Ravisankar T.; Kailasam M.; Jayakumar R.; Subburaj R.; Shinoj P.; Rajni Jain; Lal K. K.; Patil P. K. (Aquaculture International, 2025)

KERN-HIC: a hyperspectral remote sensing model for land cover classification and land use monitoring - Ganesh Babu R.; Geetha T. S.; Arul S.; Kavin Kumar K. (Environmental Monitoring and Assessment, 2025)

Effects of silica on stored product pest, Sitophilus oryzae L. (Coleoptera: Curculionidae) and its residual impact on Triticum aestivum L. grain - Parthiban Packirisamy; Baharani Soren; T. Geetha; C.S. Vivek Babu; S. Ezil Vendan (Journal of Stored Products Research, 2025)

Enhancing earth target classification in hyperspectral imagery using graph convolutional neural networks and graph-regularized sparse coding - Geetha T S; Chellaswamy C; Kaliraja T; Ramachandra Reddy K (Remote Sensing Applications: Society and Environment, 2025)

Effects of Metarhizium anisopliae on the histochemistry and enzymatic activities of Helicoverpa armigera (Hübner, 1809) - Yamini R; Shanmugam P.S; Murugan M; Geetha N; Meenakshi P; Srinivasan T; Premalatha K; Kandan A; Sathiyaraj G; Vivekanandhan P (Biocatalysis and Agricultural Biotechnology, 2024)

Comprehensive river water quality monitoring using convolutional neural networks and gated recurrent units: A case study along the Vaigai River - Geetha T. S; Gandhimathi G; Chellaswamy C; Thiruvalar Selvan P (Journal of Environmental Management, 2024)

Deep learning for river water quality monitoring: a CNN-BiLSTM approach along the Kaveri River - T. S. Geetha; C. Chellaswamy; E. Raja; K. Venkatachalam (Sustainable Water Resources Management, 2024)

Enhancing remote target classification in hyperspectral imaging using graph attention neural network - T S Geetha; C Subba Rao; C Chellaswamy; K Umamaheswari (Journal of Earth System Science, 2024)

Revealing Adaptability of Sugar Beet (Beta vulgaris) Genotypes Through Environmental Interaction (GEI) connecting Variations in Tuber Yield - M. Shanmuganathan; D. Kumaresan; S. Geetha; M. Dhasarathan; M. Jayaramachandran; R. Sudhagar; T. Selvakumar; L. Chitra; S. Mohan; A. Gurusamy; K. Iyanar (Agricultural Research, 2023)

Solving electric power distribution uncertainty using deep learning and incentive-based demand response - Balakumar Palaniyappan; Vinopraba T; Geetha Chandrasekaran (Utilities Policy, 2023)

Biochemical profiling of ‘toko’ (Livistona jenkinsiana griff.): An endangered underutilized fruit of north east India - T. Yatung; V. Bhargav; K.S. Shivashankara; G.A. Geetha; A.N. Lokesha (Biochemical Systematics and Ecology, 2023)

Usage pattern of chemicals, biologicals and veterinary medicinal products in Indian aquaculture - Prasanna K. Patil; Sudhansu S. Mishra; Pravata K. Pradhan; Sanjib K. Manna; Jawahar T. Abraham; Haresh G. Solanki; Neetu Shahi; Priyabrata Swain; Satya N. Sahoo; Satheesha Avunje; Krupesha S. R. Sharma; Rajamanickam Geetha; et al. (Reviews in Aquaculture, 2022)
The use of chemicals, biologicals and veterinary medicinal products (VMPs) helps in healthy and sustainable fish production. Information on the use of these products is essential for assessing farming practices, potential human health and environmental risks. A questionnaire‐based nationwide survey covering aquaculture farms ( n = 2936) producing carps, tilapia, pangasius and rainbow trout in freshwater and shrimp in brackishwater estimated the use of 52 different types of inputs which included disinfectants (597 g t −1 ), probiotics (2.28 kg t −1 ), environmental modifiers (22.82 kg t −1 ), nutritional supplements (1.96 kg t −1 ), natural anti‐infective agents (293 g t −1 ), herbicide and piscicides (844 g t −1 ), antibiotics (2 mg PCU −1 ), antifungal (4 mg PCU −1 ), and antiparasitic (14 mg PCU −1 ) agents. The bulk of these inputs was used for soil and water quality improvement and had low environmental and human safety concerns. The multivariate analysis revealed significant variation in the frequency and quantity of compounds use among farm groups. Redundancy analysis revealed a significant association between the number of products used and stocking density. The survey also showed a considerable influence of education and farming experience on the usage pattern of aquaculture inputs. Results of the study indicated greater reliance of farmers on the use of disinfectants for biosecurity, nutritional supplements for enhanced growth and environmental modifiers for maintaining soil and water quality in culture systems. Though there was no use of restricted antibiotics and antiparasitic agents, the development and implementation of standard regulatory guidelines are essential for safe and effective use of inputs for sustainable aquaculture.

Characterisation of an individual of the giant form of the purpleback flying squid Sthenoteuthis oualaniensis (Cephalopoda: Ommastriphidae) in the Arabian Sea and its biological descriptors - Kurichithara K. Sajikumar; Theparambil M. Najmudeen; Nadakkal Ragesh; N. S. Jeena; Summaya Rahuman; K. T. Sadanandan Sunil; Geetha Sasikumar; Kolliyil S. Mohamed (Molluscan Research, 2021)

Role of physical oceanography parameters in ocean’s biological response with the passage of cyclone Titli in the Bay of Bengal - K Vijay Prakash; Ch S Geetha Vimala; P V Nagamani; N K Baranval; Shivashankar Manche; T Preethi Latha; I V G Bhavani; Y Umamaheswara Rao; Ch S N Phanindra; K Srinivas; K P Kumari (Journal of Earth System Science, 2021)

Assessment of Water Quality Along the Southeast Coast of India During COVID-19 Lockdown - K. Vijay Prakash; Ch. S. Geetha Vimala; T. Preethi Latha; Chiranjivi Jayaram; P. V. Nagamani; Ch. N. V. Laxmi (Frontiers in Marine Science, 2021)
The COVID-19 pandemic has affected the entire world and has had a devastating impact on both lives and livelihoods in India. The only way to defeat the rapid spread of COVID-19, is to shut down socio-economic activities and to maintain minimal human interaction with the implementation of a lockdown. Such lockdowns have manifested in a pollution curtailment in almost all spheres of the planet, including in marine pollution. Quantifying this decrease in pollution levels enables the scientific community to assess the contribution of anthropogenic (especially non-essential) activities to global/regional pollution levels. This paper aims to study the impact of the stringent lockdown period (phase 1 and 2) on coastal water quality along the Chennai coast of India, by analyzing suspended matter concentration (SPM), a key element of water quality and diffuse attenuation coefficient, K d (490), using LANDSAT-8 Operational Land Imager (OLI) data. LANDSAT-8/OLI, L1TP scenes were subjected to radiometric calibration and atmospheric correction to derive surface reflectance values from raw digital numbers using ACOLITE software and a brief insight has been given for the Dark Spectrum Fitting algorithm used in ACOLITE. SPM concentration decreased by 15.48 and 37.50% in the Chennai and Ennore ports, respectively, due to minimal vessel movement and cargo handling. The stringent lockdown led to the operation of fewer thermal plant units, thus less fly ash was emanated, resulting in a 28.05% reduction in SPM levels over Ennore creek. As industrial and commercial activities subsided, the city’s water bodies became clearer than they were just a fortnight prior to the lockdown, with a reduction of 22.26% of SPM in Adyar and 33.97% in Cooum riverine estuaries. Decrease in K d (490) showed a positive relationship with SPM and thus improved coastal water quality because of the reduction of SPM during this period. The variations in PM2.5 and PM10 concentrations were studied using National Air Quality Monitoring Programme (NAMP) data and reduced levels in particulate matter concentration (PM2.5 and PM10) for the Adyar residential area (24.38 and 28.43%) and for the Nungampakkam commercial area (36.09 and 67.18%) were observed. A significant reduction in PM2.5 concentration (45.63%) was observed in the Ennore-Manali Industrial region.

Trends, causes, and indices of import rejections in international shrimp trade with special reference to India: a 15-year longitudinal analysis - R. Geetha; T. Ravisankar; P. K. Patil; Satheesha Avunje; S. Vinoth; C. V. Sairam; K. K. Vijayan (Aquaculture International, 2020)

Agronomic Response, Weed Smothering Efficiency and Economic Feasibility of Sugarcane and Legume Intercropping System in Tropical India - P. Geetha; A. S. Tayade; C. A. Chandrasekar; T. Selvan; Rajesh Kumar (Sugar Tech, 2019)

From Science to Evidence – How Biodiversity Indicators Can Be Used for Effective Marine Conservation Policy and Management - Abigail McQuatters-Gollop; Ian Mitchell; Cristina Vina-Herbon; Jacob Bedford; Prue F. E. Addison; Christopher P. Lynam; P. N. Geetha; Estee Ann Vermeulan; Kaylee Smit; Daniel T. I. Bayley; Elisabeth Morris-Webb; Holly J. Niner; et al. (Frontiers in Marine Science, 2019)

Impact of the Charge Ratio on the In Vivo Immunogenicity of Lipoplexes - Zahra Heidari; Jaspreet S. Arora; Dibyadyuti Datta; Vijay T. John; Nirbhay Kumar; Geetha P. Bansal (Pharmaceutical Research, 2017)

Anti-tuberculosis drug concentrations in tuberculosis patients with and without diabetes mellitus - A K Hemanth Kumar; V Chandrasekaran; T Kannan; A Lakshmi Murali; J Lavanya; V Sudha; Soumya Swaminathan; Geetha Ramachandran (European Journal of Clinical Pharmacology, 2017)

The MEK/ERK pathway is the primary conduit for Borrelia burgdorferi-induced inflammation and P53-mediated apoptosis in oligodendrocytes - Geetha Parthasarathy; Mario T. Philipp (Apoptosis, 2014)

SCS-CN-based Continuous Simulation Model for Hydrologic Forecasting - K. Geetha; S. K. Mishra; T. I. Eldho; A. K. Rastogi; R. P. Pandey (Water Resources Management, 2008)

Heterologous expression of Bluetongue VP2 viral protein fragment in Pichia pastoris - T. N. Athmaram; Geetha Bali; Goon G. Kahng; Sulatha Dwarakanath (Virus Genes, 2007)

Faecal fat content in healthy adults by the ‘acid steatocrit method’ - Anita R. Bijoor; S. Geetha; T. Venkatesh (Indian Journal of Clinical Biochemistry, 2004)

A small molecule antagonist of the α v β3 integrin suppresses MDA-MB-435 skeletal metastasis - John F. Harms; Danny R. Welch; Rajeev S. Samant; Lalita A. Shevde; Mary E. Miele; Geetha R. Babu; Steven F. Goldberg; Virginia R. Gilman; Donna M. Sosnowski; Dianalee A. Campo; Carol V. Gay; Lynn R. Budgeon; et al. (Clinical & Experimental Metastasis, 2004)

Effect of lupeol and lupeol linoleate on lysosomal enzymes and collagen in adjuvant-induced arthritis in rats - T. Geetha; P. Maralakshmi (Molecular and Cellular Biochemistry, 1999)

Antifungal Activity of Some B,D-Seco Limonoids from Two Meliaceous Plants - T. R. Govindachari; G. Suresh; B. Banumathy; S. Masilamani; Geetha Gopalakrishnan; G. N. Krishna Kumari (Journal of Chemical Ecology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Identification of antifungal compounds from the seed oil ofAzadirachta Indica - T. R. Govindachari; G. Suresh; Geetha Gopalakrishnan; Balaganesan Banumathy; S. Masilamani (Phytoparasitica, 1998)

Parasites, predators and other arthropods associated withMusca domestica and other flies breeding in bovine manure - M. Geetha Bai; T. Sankaran (BioControl, 1977)